Spontaneous copolymerization of maleic anhydride and N-vinylimidazole in 1,4-dioxane .1. Charge transfer complexation and kinetics of the copolymerization - Goksel, C; Hacioglu, B; Akbulut, U (John Wiley & Sons Inc, 1997)
Maleic anhydride (MAH) and N-vinylimidazole (NVIM) were found to form a charge transfer complex in 1,4-dioxane. The equilibrium constant, K, of the complex and its composition were calculated from the modified Benesi-Hildebrand equation by using UV spectrophotometry. Spontaneous copolymerization of MAH and NVIM has been studied in the range from 20 to 80 mol % MAH in the feed. The effects of the polymerization temperature, monomer feed composition, and total monomer concentration on the initial rate of polymerization were investigated. The values of overall activation energy, E-a, and overall order with respect to total monomer concentration were calculated. Copolymer compositions were found from the elemental analysis data. Reactivity ratios were calculated by the extended Kelen-Tudos method. (C) 1997 John Wiley & Sons, Inc.
Keywords: N-vinylimidazole; maleic anhydride; spontaneous copolymerization; charge transfer complex; kinetics